Frequency of antinuclear antibodies in normal healthy population in Pakistan - Atif, Amin Baig; Salman, Amiruddin; Mohd Khairi, Zahri@Johari (2017)
The autoimmune disorders and auto antibodies are rapidly becoming a major cause of concern in the medical field. Antinuclear antibody plays a significant role in autoimmunity and it is targeted against different nuclear antigens. Although its elevated levels are found in autoimmune disorders but it is also synthesized in healthy individuals. The study objective is to determine the frequency of antinuclear antibodies in healthy individuals in Pakistan. Blood samples of 587 (503 females and 84 males) individuals were taken through convenience sampling technique. Serum was separated by centrifugation and then ANA titer was determined by Enzyme Linked Immunosorbent Assay (ELISA). SPSS version 20.0 (IBM-SPSS, Inc, Armonk, New York) was used for statistical calculations. ANA autoantibodies were found only in 6 individuals, out of which 5 were females and 1 was male.No significant association of antinuclear antibodies was observed between males and females. Evaluation of the incidence of ANA in general population is important to ensure its reliability as a biomarker of disease. Current study found very low occurrence of ANA in general population which indicates its exclusive association with the diseases especially autoimmune diseases. The one percent positive cases can be further followed up for being at risk of developing disease.